A REVIEW ON THE ROLE OF HOMOEOPATHY IN EPIDEMICS AMIDST COVID-19 CRISIS - Ashish Shivadikar (International Journal of Ayurveda and Pharma Research, 2020)
It is a challenging time for the entire medical world to manage Coronavirus diseases 2019 (COVID-19). The past few decades there is increase of epidemic diseases, with increase loss of lives due to rapidly spreading devastating epidemics; there is a need for protective immunization and prevention. The great hope in the control of infectious diseases is always vaccine. Vaccines have played an important part in the reduction of communicable diseases. However, Vaccines are continually monitored for safety, and like any medication, vaccine can cause side effects. Homoeopathy has been reportedly used with variable degree of success in influenza, cholera and other epidemics for 200 years. Homoeopathy has been used both therapeutically and /or prophylactic with success in past, using different approaches like Genus epidemicus, nosodes, and homoeopathic formulations.